ADFP promotes cell proliferation in lung adenocarcinoma via Akt phosphorylation. Issue 2 (29th November 2020) - Meng, Xia; Sun, Ruiying; Wang, Wei; Zhang, Na; Cao, Shiguang; Liu, Boxuan; Fang, Ping; Deng, Shanshan; Yang, Shuanying
Abstract: Previously, we identified differentially expressed proteins, including ADFP, between lung adenocarcinoma (LAC) tissue and paired normal bronchioloalveolar epithelium. In this study, we investigated the role of ADFP in LAC. ADFP levels in the serum of patients with lung cancer and benign diseases were measured by enzyme‐linked immunosorbent assays (ELISA). shRNA was used to knock‐down or overexpress ADFP in A549 and NCI‐H1299 cells. The biological function of ADFP and its underlying mechanisms was evaluated in vivo and in vitro. ADFP was highly expressed in the serum of lung cancer patients, especially those with LAC. ADFP promoted cell proliferation and up‐regulated the p‐Akt/Akt ratio in A549 and NCI‐H1299 cells in vitro. Furthermore, in nude mice, ADFP promoted tumour formation with high levels of p‐Akt/Akt, Ki67 and proliferating cell nuclear antigen (PCNA). Similar to the effect of ADFP knock‐down, MK‐2206 (a phosphorylation inhibitor of Akt) reduced A549 and NCI‐H1299 cell proliferation. In ADFP‐overexpressing A549 and NCI‐H1299 cells, proliferation was suppressed by MK‐2206 and returned to the control level. ADFP did not regulate invasion, migration or adhesion in LAC cells. Together, these results suggest that ADFP promotes LAC cell proliferation in vitro and in vivo by increasing Akt phosphorylation level.